Pomalidomide in relapsed and refractory multiple myeloma: multicenter retrospective study - V. G. Potapenko; E. V. Baumert; A. A. Bobrova; R. V. Vashchenkov; N. V. Dorofeeva; K. D. Kaplanov; E. V. Karyagina; A. N. Levanov; A. S. Luchinin; S. I. Moiseev; A. V. Novitskii; A. S. Nizamutdinova; et al. (Онкогематология)
Background. The treatment options for patients with multiple myeloma who refractory to previous bortezomib and lenalidomide therapy are limited. Pomalidomide is ап immunomodulatory agent that was registered for the treatment of patients with double refractory multiple myeloma.Aim. To evaluate efficacy, safety and optimal course of the therapy with pomalidomide in routine practice in patients with double refractory multiple myeloma.Materials and methods. Overall, 71 patients with double refractory multiple myeloma were included in the retrospective analysis. There were 36 males and 35 females. The median age was 61 years (range 35-79). According to Durie-Salmon staging system, there were 53 (79.1 %) patients in stage III, 13 (19.4 %) - stage II, and 1 (1.5 %) - stage I.The stage was unknown in 4 patients. Kidney impairment at the onset was in 10 (15 %) patients, the normal function was in 57 (85 %) patients and 4 patients had no data. Most patients (n = 68, 95.8 %) received pomalidomide in one therapy line, in 3 (4.2 %) patients - drug was given in two lines, totally 74 episodes of use. Median number of drugs prescribed prior to pomalidomide were 4 (2-9) drugs, including target ones - 2 (2-5). In the first remission 31 (43.6 %) patients received high-dose therapy with autologous stem cell transplantation. pomalidomide was administered in combination with low doses of dexamethasone (PomDex, n = 44; 59.4 %) and as a part of triple regimens (n = 30; 40.6 %). previously exposed (n = 22; 73.3 %) and new drugs (n = 8; 26.7 %) were used in the combination treatment. In 44 (61.9 %) patients pomalidomide was administered more than 3 years after the onset of the disease, median 63.5 (37-184) months. In 27 (38.1 %) patients it was given within less than 3 years after the onset, median 21 (6-36) months. The primary endpoint was progression-free survival. Secondary endpoints - pomalidomide tolerability, response rate and optimal third drug in the triple regimen. The dependence of progression-free survival, frequency of response and adverse events from the pretreatment, the choice of the third drug, gender, age, immunochemical variant, stage according to the International Staging System and to Durie-Salmon classification was studied.Results. The median time from the diagnosis to the start of pomalidomide therapy was 44.5 (6-184) months. The median of cycles with pomalidomide was 3 (1-30). The response was achieved in 52 (70 %) patients. The median progression-free survival was 4 (1-30) months, overall survival - 6 (0.5-42) months. Adverse effects were noted in 34 (46.5 %) patients. The most frequent adverse events were neutropenia grade III-IV (n = 14; 41.3 %), infection (n = 7; 20.7 %) and fatigue with limitation of daily activity (n = 6; 20.6 %). The rate of adverse events was higher in patients with triplets than doublets regimens of therapy: 43.3 % (n = 13) and 27.2 % (n = 12) respectively (p = 0.008). There were no statistically significant differences in progression-free survival between pomalidomide treatment options (two- or three-component regimen).Conclusion. Compared to the three-component therapy consisting of drugs to which refractoriness was previously diagnosed the PomDex scheme is less toxic and equally effective. Therapy with pomalidomide is effective in the majority of patients with double refractory multiple myeloma even in heavily pretreated. The toxicity is acceptable.